Pengembangan Kemampuan Bahasa Anak Dengan Menggunakan Media Bola Huruf - Elfarini Susanti; Desri Wahyuni; Mezi Rahmayanti (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research is motivated by the low fine Language of Group B children at TK Dharmawanita Labuah Gunuang in Labuah Gunuang Village. One solution to address this issue is to implement Compile Letter Ball activities. This study aims to improve fine Language in Group B at TK Dharmawanita Labuah Gunuang in Labuah Gunuang Village. The research method used in this study is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, with two meetings in each cycle. Data collection techniques used were observation and documentation. The results of this research show an improvement in children's scores from the pre-action phase, Cycle I, to Cycle II, which can be described as follows: In the pre-action phase, 7 children or 63.64% had low scores (BB), then in Cycle 1, this decreased to 3 children or 27.27%, and in Cycle II, it became 0 children or 0%. The moderate score (MB) in the pre-action phase was 2 children or 18.18%, then in Cycle 1, it became 2 children or 18.18%, and in Cycle II, it became 0 children or 0%. The high score (BSH) in the pre- action phase was 1 child or 9.09%, then in Cycle 1, it became 3 children or 27.27%, and it remained at 3 children or 27.27% in Cycle II. The very high score (BSB) in the pre-action phase was 1 child or 9.09%, then in Cycle 1, it became 3 children or 27.27%, and in the end, in Cycle II, it increased to 8 children or 72.73%. Based on the above research results, the researcher recommends that teachers consider implementing Compile Letter Ball activities as an alternative method to enhance children's fine Bahasa. Keywords: Language, Letter Ball , classroom action research